Early eruption in a 7-year-old girl with congenital hypothyroidism (Arequipa, Peru) - Delma Carbajal Llamosas (2017)
This case report is dental medical importance because it occurs in a girl of 7 years, usually in this type of hormonal birth defects such as congenital hypothyroidism occurs frequently delay tooth eruption , very rare thing in this ; since there is an eruption early which deserves further study would have to intervene where the pediatric dentist and Endocrinologist.